Note on chromatic polynomials of the threshold graphs - Noureddine Chikh; Miloud Mihoubi (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2019)
Let G be a threshold graph. In this paper, we give, in first hand, a formula relating the chromatic polynomial of Ḡ (the complement of G) to the chromatic polynomial of G. In second hand, we express the chromatic polynomials of G and Ḡ in terms of the generalized Bell polynomials.